Dentin bond strength: influence of Er:YAG and Nd:YAG lasers - Ribeiro, Carolina Ferraz [UNESP]; Gonçalves, Sérgio Eduardo de Paiva [UNESP]; Yui, Karen Cristina Kazue [UNESP]; Borges, Alessandra Bühler [UNESP]; Barcellos, Daphne Câmara [UNESP]; Brayner, Ricardo [UNESP] (Quintessence Publishing, 2013)
The aim of this study was to investigate the effects of Er:YAG and Nd:YAG lasers on the shear bond strength of composite resin to dentin. The coronal portion of 56 human molars was divided into three parts, and the dentin thickness was standardized at 2 mm. A 3-mm hole was marked in the center of each tooth with sealing tape paper. The specimens (n = 14) were then divided into four groups: (1) acid etching + Single Bond (SB) (control), (2) acid etching + SB + Nd:YAG laser irradiation (before adhesive curing), (3) thermal etching with the Er:YAG laser + SB, and (4) thermal etching with the Er:YAG laser + SB + Nd:YAG laser irradiation (before adhesive curing). A composite resin cylinder was built into the delimited area for conducting the shear bond strength test on the universal testing machine. The means ± standard deviations were: group 1, 17.05 ± 4.15 MPa; group 2, 16.90 ± 3.36 MPa; group 3, 12.12 ± 3.85 MPa; and group 4, 12.92 ± 2.73 MPa. Groups 1 and 2 presented significantly higher values than groups 3 and 4. It was concluded that conventional etching with 37% phosphoric acid yielded significantly higher bond strength values compared to thermal etching with the Er:YAG laser. The Nd:YAG laser did not significantly influence the bond strength.